Long Non-coding RNAs as Functional and Structural Chromatin Modulators in Acute Myeloid Leukemia - Wurm, Alexander A.; Pina, Cristina (Frontiers in Oncology, 2019)
Acute myeloid leukemia is a hematopoietic neoplasm of dismal prognosis that results from the accumulation of immature myeloid blasts in the bone marrow and the peripheral blood. It is strongly dependent on epigenetic regulation for disease onset, maintenance and in response to treatment. Epigenetic regulation refers to the multiple chemical modifications of DNA or DNA-associated proteins that alter chromatin structure and DNA accessibility in a heritable manner, without changing DNA sequence. Unlike sequence-specific transcription factors, epigenetic regulators do not necessarily bind DNA at consensus sequences, but still achieve reproducible target binding in a manner that is cell and maturation-type specific. A growing body of evidence indicates that epigenetic regulators rely, amongst other factors, on their interaction with untranslated RNA molecules for guidance to particular targets on DNA. Non (protein)-coding RNAs are the most abundant transcriptional products of the coding genome, and comprise several different classes of molecules with unique lengths, conformations and targets. Amongst these, long non-coding RNAs (lncRNAs) are species of 200bp to >100K bp in length, that recognize and bind unique and largely uncharacterized DNA conformations. Some have been shown to bind epigenetic regulators, and thus constitute attractive candidates to mediate epigenetic target specificity. Herein, we postulate that lncRNAs are central players in the unique epigenetic programming of AML and review recent evidence in support of this view. We discuss the value of lncRNAs as putative diagnostic, prognostic and therapeutic targets in myeloid leukemias and indicate novel directions in this exciting research field.